Galaxy mergers in a fractal cosmology - Bruno J. Souza; Osvaldo L. Santos-Pereira; Marcelo B. Ribeiro (European Physical Journal C: Particles and Fields)
Abstract This work discusses the influence of galaxy mergers in the evolution of a parabolic Lemaître–Tolman–Bondi (LTB) cosmology with simultaneous big bang endowed with two consecutive single fractal galaxy distributions systems possessing fractal dimension D. Based on recent empirical findings, it is assumed that the resulting galaxy mass from mergers can be expressed by a redshift dependent decaying power law. The proposed cosmological model modifies the relativistic fractal number counts distribution by including a merger rate evolution that estimates the model’s radial density. Numerical solutions for the first order small-merger-rate approximation (SMRA) are found and the results show that a fractal galaxy distribution having $$D=1.5$$ D = 1.5 in the range $$0.1<z<1.0$$ 0.1 < z < 1.0 , and $$D=0.5$$ D = 0.5 for $$1<z<6$$ 1 < z < 6 , as suggested by recent empirical findings, the SMRA allows consistent description of the model for a merger rate power law exponent up to $$q=0.2$$ q = 0.2 considering a fractal galaxy distribution starting from the Local Group. Consistent values were also found up to $$q=2.5$$ q = 2.5 and $$z=7$$ z = 7 from a scale smaller than the Local Supercluster. These results show that galaxy mergers can be successfully incorporated into the dynamics of a parabolic LTB fractal cosmology.